Hybrid MAC protocols in VANET: A survey - Mohamed Zain, I.F. (Springer Verlag, 2017)
Various ongoing research efforts in Vehicular Ad hoc Network (VANET) related to safety and non-safety applications have been published in academia and industry. One of the main areas in VANET that is still lacking of significant research contributions is toward designing reliable Medium Access Control (MAC) protocols. Existing surveys on MAC protocols in VANET mostly discuss general MAC methods, that include contention-based and contention-free MAC protocols. A hybrid MAC protocol that adopts both contention-based and contention-free MAC, proposed to enhance the network performance in VANET, is fruitful to be explored further. Hence, a survey of hybrid MAC protocols for VANET is presented in this paper. The benefits and limitations of the existing hybrid MAC protocols are discussed based on their classification to provide some insights into the recent advancement of high-performance MAC protocols for vehicular networks. Finally, some open research issues are highlighted as part of future research directions that need further investigations. © Springer Nature Singapore Pte Ltd. 2017.